The Role of Parents in Supporting the Education of Daughters Continuing Their Study in Higher Education - Yani Liligoly; Fatimah Sialana; Agus Soumokil (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is a qualitative descriptive research that aims to find out how society views education for girls and what is the role of parents in supporting girls' education in tertiary institutions. This research was conducted in Waelo Village, Fena Fafan District, South Buru Regency. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved. The results of this study can show that the role of parents in educating their daughters to a higher level is still very minimal. Education as an effort to educate the nation's children was apparently not obtained by some girls, especially girls who were in Waeleo Village, Fena Fafan District, South Buru Regency. This happened because of the attitude of parents who did not want their daughters to continue their studies at tertiary institutions. There are several factors that cause parents not to allow their daughters to continue their education to tertiary institutions, namely the first for economic reasons. Economic reasons are the basic reason for parents, because they are considered unable to pay, besides that, parents have the perception that there is no use and benefit if girls are sent to school because in the end they will become housewives, and because many events that often occur are pregnancies that befall women while they are still in school. It is these factors that make parents not allow their daughters to continue their education to a higher level. Seeing problems like this, the local government took steps to educate parents about the importance of education, as well as provide cash assistance to people who experience economic constraints in sending their children to school.